LANDFILL STABILITY ANALYSIS USING CORRUGATED CONCRETE SHEET PILE (CCSP) WITH PLAXIS 2D V22 SOFTWARE - Jumadi, Kardina; Dofir, Akhmad; Andreas, Azaria; Tinumbia, Nuryani (Jurnal Infrastruktur, 2024)
Landfill in road projects requires a stable condition before it can be continued on further work. The stability factor of the landfill depends on the bearing capacity of the subgrade, the shear strength of the soil, the planned elevation, and the angle of inclination of the landfill. This research is located on one side of the Jagorawi Toll road and the Bogor Outer Ring Road, near the South Sentul Toll exit gate. The results of the soil investigation obtained a clay type soil classification at a depth of 0 – 13 m (N-SPT value 3-5). Initial analysis shows the need for landfill height, varies along the road (ranging 4.9 m - 2.4 m). The purpose of this research is to compare the stability of the landfill in the following 2 conditions, 1st condition from STA 1+789 – STA 1+850 (4.9 m height of landfill) using Corrugated Concrete Sheet Pile (CCSP) reinforcement on the left and right of the road side with a 2 m deep geotextile layer, and 2nd condition from STA 1+850 – STA 1 +950 (2.4 m height of landfill) does not use any reinforce. The research approach uses quantitative descriptive, research data including other soil classifications, bor logs, N-SPT values, soil properties from samples (C, Ø, γ, etc.) taken from the site. Apart from that, data on the geotextile and CCSP parameters that will be used is also needed. Analysis was carried out using the Finite Element approach and Plaxis 2D V22 software. The results show that in 1st condition, the safety factor value is 3.7, where the reinforcement system provided is able to withstand 3.7x the working load (vehicles and active soil). Meanwhile, on the 2nd condition produces a safety factor value of 5.2. The analysis results show that these 2 areas have a safety factor that exceeds the existing literature requirements, namely 1.5.